Population pharmacokinetics and exposure‐response analysis of a single dose of sotrovimab in the early treatment of patients with mild to moderate COVID‐19 - Jennifer E. Sager; Asma El‐Zailik; Julie Passarell; Stefan Roepcke; Xiaobin Li; Melissa Aldinger; Ahmed Nader; Andrew Skingsley; Elizabeth L. Alexander; Wendy W. Yeh; Erik Mogalian; Chad Garner; et al. (Wiley, 2023)
Abstract Sotrovimab is a recombinant human monoclonal antibody that has been shown to prevent progression to hospitalization or death in non‐hospitalized high‐risk patients with mild to moderate coronavirus disease 2019 following either intravenous (i.v.) or intramuscular (i.m.) administration. Population pharmacokinetic (PopPK) and exposure‐response (ER) analyses were performed to characterize single dose sotrovimab pharmacokinetics (PK) and the relationship between exposure and response (probability of progression), as well as covariates that may contribute to between‐participant variability in sotrovimab PK and efficacy following i.v. or i.m. administration. Sotrovimab PK was described by a two‐compartment model with linear elimination; i.m. absorption was characterized by a sigmoid absorption model. PopPK covariate analysis led to the addition of the effect of body weight on systemic clearance and peripheral volume of distribution, sex on i.m. bioavailability and first‐order absorption rate (KA), and body mass index on KA. However, the magnitude of covariate effect was not pronounced and was therefore not expected to be clinically relevant based on available data to date. For ER analysis, sotrovimab exposure measures were predicted using the final PopPK model. An ER model was developed using the exposure measure of sotrovimab concentration at 168 h that described the relationship between exposure and probability of progression within the ER dataset for COMET‐TAIL. The number of risk factors (≤1 vs. >1) was incorporated as an additive shift on the model‐estimated placebo response but had no impact on overall drug response. Limitations in the ER model may prevent generalization of these results to describe the sotrovimab exposure‐progression relationship across severe acute respiratory syndrome‐coronavirus 2 variants.